К ревизии рода аристотерева — Aristolliereva Fгеу (Diplera, Therevidae) — Палеоарктики. Сообщение I - Зайцев, В.Ф. (Вестник зоологии, 1971)
The article deals with a description of four new spccies of the genus Aristothereva
from the Middle and Central Asia: Aristothereva eversmanni Zaitze v sp. п., A. kozlovi Zaitze v sp. п., A. variabilis Zaitze v sp. п., Л. angustifrons Zaitze v sp. n